THE POWER OF BODY LANGUAGE IN EFFECTIVE COMMUNICATION - Qarshiyeva Barchin Abdimurodovna; Karshiyeva Gulsinaxon Toʻlqin qizi; Jumayeva Durdona Malikovna (TADQIQOTLAR, 2025)
Abstract Body language, encompassing gestures, facial expressions, posture, and eye contact, is a critical component of human communication, often conveying more than verbal language. This article explores the power of body language in shaping interpersonal interactions, with a focus on its applications in professional, social, and cross-cultural contexts. Through comparative analysis of body language practices in the United States, China, Brazil, and Uzbekistan, we examine how cultural norms influence nonverbal communication and its interpretation. The findings highlight the importance of understanding body language to enhance communication effectiveness, build trust, and avoid misunderstandings. This study offers practical strategies for leveraging body language in diverse settings, contributing to communication scholarship and intercultural competence.